Perbedaan Hasil Belajar Siswa dalam Penggunaan Teknologi di Pondok Pesantren Al Amien pada Materi Pythagoras - Muhlisatul Mahmudah; Sholahudin Al’ayubi; Ahmad Jauhari Mahfudh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to determine the differences in mathematics learning outcomes between boarding and non-boarding students using the Desmos application at Pondok Pesantren Al Amien. This research uses a comparative quantitative method with a posttest-only design. The subjects consisted of 20 eighth-grade students divided into two groups: 10 boarding and 10 non-boarding students. The instruments used were learning outcome tests and student perception questionnaires. Data were analyzed using the Independent Sample T-Test via SPSS. The results showed a significant difference between the two groups, with non-boarding students scoring higher. This is supported by a significance value of 0.010 (< 0.05). Learning with the Desmos application is proven effective in improving mathematics achievement, especially for students with better access to technology.